Political and Economic Integration in Africa: A Case of Marking Time? - Soori, Batuuroh I. P.; Masereka, Alice Kisembo; Apedoe-Dzidza, Dina Yawa (Journal of Business and Retail Management Research, 2007)
This paper looks at some of the reasons for the existence of the phenomena of political and economic integration in Africa. The paper addresses what the concepts of integration mean. It also examines some of the theoretical frameworks and approaches to integration. The paper further tries to answer the question, why is integration important? This is examined from the point the challenges confronting African. The article however moves on to address the reality on the ground. It looks at some of the issues causing the contingent to keep ‘marking time’. Since the days of the Organisation of African Unity; Unity has arguable eluded Africa. .These include the multiplicity of regional groups, sheer lack of Political and the division between the so-called ‘gradualists’ and ‘radicals’. For integration to flourish and help address African’s numerous problems, the ruling elites will have to recommit themselves to integration and not rely on rhetoric’s. Ordinary Africans and the African Diaspora must as a matter of necessity is at the core of integration in Africa. These are some of the recommendations outlined to help get integration off its marks.
Keywords: Regional Economic Communities; African Economic Community; Political and Economic Integration